Penerapan Metode Pengamatan Objek Langsung di Kelas dalam Meningkatkan Kemampuan Menulis Puisi Bebas di Sekolah Menengah Pertama - Rahmatiah Rahmatiah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
Abstract: Application of Direct Object Observation Method in the Classroom in Improving Free Poetry Writing Skills in Junior High School. This study aims to determine the implementation of the method of observing objects directly in class in improving the ability to write free poetry in junior high school. This research approach uses a qualitative approach with the type of classroom action research using research procedures including: planning, implementing actions, observation and reflection. The location of this research was carried out at SMP Negeri 5 Mandai. The results showed that there was an increase in student learning activities from cycle I to cycle II, namely the increase in the number of students in listening to teacher explanations, asking questions, answering questions, student learning outcomes also increased, namely the total score obtained in cycle I of 555 and in cycle II of 958. So that the application of the direct object method can improve student learning outcomes in junior high school.